KEWENANGAN DEWAN PERWAKILAN DAERAH DI BIDANG LEGISLASI - I Nyoman Wahyu Sukma Suriyawan; I Wayan Novy Purwanto (Kertha Negara : Journal Ilmu Hukum, 2014)
Authority to legislate as embedded within 1945 National Constitution shall be performed by both government and senate, meanwhile regional senate (“DPD”) which is also categorized as legislative body does not enjoy such authority, as it is enunciated within Law No 27 of 2009 concerning MPD, DPR, DPD, and DPRD along with Law No 12 of 2011 concerning Procedure of Drafting an Act which also reduced the authority of DPD. As explained, problems risen and shall be observed is whether the implication of mentioned laws towards the authority of DPD and also after the Judgment of Constitutional Court No. 92/PUU-X/2012. Method of research applied shall be normative legal research combined with statutory approach. Conclusion drawn from the research shall be, due to the Judgment of the Constitutional Court, DPD shall enjoys the right to enter into the drafting of national legislation program, along with the discussion on budgeting and autonomy issue, however its right to pass a draft into a law remain absent.